First record of Stenodiplosis sorghicola on sorghum in Greece - Tsagkarakis, A. E.; Emmanouel, N. G.; Scarakis, G. N. (ENTOMOLOGIA HELLENICA, 2011)
In October 2007, the sorghum midge Stenodiplosis sorghicola (Coquillett) (Diptera: Cecidomyiidae) was recorded for the first time in Greece. Its occurrence was noticed in an experimental sorghum cultivar at Aliartos, near Athens, in Viotia region. Information on its morphology, biology and distribution is given.